Are Dark Energy and Dark Matter Different Aspects of the Same Physical Process? - Kastner, Ruth E.; Kauffman, Stuart (Frontiers in Physics, 2018)
It is suggested that the apparently disparate cosmological phenomena attributed to so-called ‘dark matter’ and ‘dark energy’ arise from the same fundamental physical process: the emergence, from the quantum level, of spacetime itself. This creation of spacetime results in metric expansion around mass points in addition to the usual curvature due to stress-energy sources of the gravitational field. A recent modification of Einstein’s theory of general relativity by Chadwick, Hodgkinson, and McDonald incorporating spacetime expansion around mass points, which accounts well for the observed galactic rotation curves, is adduced in support of the proposal. Recent observational evidence corroborates a prediction of the model that the apparent amount of ‘dark matter’ increases with the age of the universe. In addition, the proposal leads to the same result for the small but nonvanishing cosmological constant, related to ‘dark energy,’ as that of the causet model of Sorkin et al.